Cost‐effectiveness of first trimester non‐invasive fetal RHD screening for targeted antenatal anti‐D prophylaxis in RhD‐negative pregnant women: a model‐based analysis. (10th December 2015) - Neovius, M; Tiblad, E; Westgren, M; Kublickas, M; Neovius, K; Wikman, A
Abstract : Objective: To estimate the cost‐effectiveness of first trimester non‐invasive fetal RHD screening for targeted antenatal versus no routine antenatal anti‐D prophylaxis (RAADP) or versus non‐targeted RAADP. Design: Model based on a population‐based cohort study. Setting: The Swedish health service. Population: Intervention subjects in the underlying cohort study were RhD‐negative pregnant women receiving first trimester fetal RHD screening followed by targeted anti‐D in 2010–2011 ( n = 6723). Historical comparators were RhD‐negative women who delivered in 2008–2009 when standard care did not include RAADP ( n = 7099). Methods: Healthcare costs for the three strategies were included for the first and subsequent pregnancies. For the comparison with non‐targeted RAADP, the immunisation rate was based on the observed rate for targeted therapy and adjusted downwards by removing the influence of false negatives. Main outcome measure: Additional cost per RhD immunisation averted. Results: Compared with RAADP, targeted prophylaxis was associated with fewer immunisations (0.19 versus 0.46% per pregnancy) and lower costs (cost‐savings of €32 per RhD‐negative woman). The savings were from lower costs during pregnancy and delivery, and lower costs of future pregnancies through fewer immunisations. Non‐targeted anti‐D was estimated to result in 0.06% fewer immunisations and an additional €16 in cost‐savings per mother, compared with targeted anti‐D. Conclusion: Based on effect data from a population‐based cohort study, targeted prophylaxis was associated with lower immunisation risk and costs versus no RAADP. Based on effect data from theoretical calculations, non‐targeted RAADP was predicted to result in lower costs and immunisation risk compared with targeted prophylaxis. Tweetable abstract: Fetal RHD screening and targeted prophylaxis resulted in lower immunisation risk and costs compared with no RAADP. Tweetable abstract: Fetal RHD screening and targeted prophylaxis resulted in lower immunisation risk and costs compared with no RAADP.